Alterations in subgingival microbiota during full‐fixed appliance orthodontic treatment—A prospective study. (25th September 2021) - Chen, Isaac; Chung, Jennifer; Vella, Raven; Weinstock, George M.; Zhou, Yanjiao; Jheon, Andrew H.
Abstract: Background: Full‐fixed appliance orthodontic treatment (commonly called braces) increases plaque accumulation and the risk of gingivitis and periodontitis. However, little consensus exists on changes to subgingival microbiota and specific periodontopathogens during treatment with braces. Prior studies have been hampered by selection biases due to dependence on culture conditions, candidate‐based PCR and shallow sequencing methods. Objective: The objective was to provide the first longitudinal, culture‐free and deep‐sequence profiling of subgingival bacteria in subjects during early stages of full‐fixed orthodontic treatment. Methods: We performed 16S rRNA next‐generation sequencing (NGS) on 168 subgingival samples collected at 4 distinct mandibular tooth sites per subject before (0 weeks) and during (6 and 12 weeks) orthodontic intervention in 9 experimental and 5 control subjects not undergoing treatment. Results: Overall, we noted that orthodontic intervention led to increased microbial richness, accompanied by an increased incidence of localized gingivitis/mild periodontitis in subjects requiring orthodontic treatment compared to controls, as well as significant baseline variations in subgingival microbiomes in all subjects. Moreover, we confirmed individual‐ and site‐dependent microbiome variability (in particular, the lingual site harboured higher microbiome diversity than buccal sites) that orthodontic bands may lead to more prolonged shifts in microbial changes compared to brackets, and evidence of adaptive enrichment of consensus bacteria with orthodontic intervention (12 novel, consensus bacterial species were identified). Conclusion: Our study, along with evolving global profiling methods and data analyses, builds a strong foundation for further analyses of subgingival microbiomes during full‐fixed orthodontic treatment.